Legal Strength Analysis of Land Ownership under Grant Sultan Status in the Indonesian Land Law System (Case Study of Supreme Court Decision Number 227-PK/PDT/2015) - Jasin Dosi Raja Simarmata; Mochammad Erwin Radityo; Fitri Rafianti (SEAN Institute, 2025)
In human life, this country is a place where people can live and live, so that this country is not separate from human actions themselves. Therefore, land is needed for everyone on this planet, which often causes problems and conflicts, especially those related to land. The formulation of the problem that is the purpose of this study is: How is the land ownership system in Indonesian law and What are the problems that arise in land ownership with the status of Grant Sultan looking at case no. 227-PK / PDT / 2015. This study uses the nature of Descriptive Analytical research. The type of research used in this study is Normative Juridical legal research obtained from secondary data. This research method uses normative juridical research, namely research based on the reason that legal research is a process of discovering legal rules, legal principles, and doctrines to answer the legal questions faced. For this reason, a rule is needed that regulates the relationship between humans and land. For humans, land is a place and space for all living things on earth, and is a source of life. On the one hand, population growth has increased and continues to accelerate, followed by the development of science and technological progress in various fields, while the country is limited natural resources.